Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.apsb.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of immune-related diseases by multiple factors of chromatin, exosomes, microparticles, vaccines, oxidative stress, dormancy, protein quality control, inflammation and microenvironment: a meeting report of 2017 International Workshop of the Chinese Academy of Medical Sciences (CAMS) Initiative for Innovative Medicine on Tumor Immunology

Abstract: Immune cells play key roles in cancer and chronic inflammatory disease. A better understanding of the mechanisms and risks will help develop novel target therapies. At the 2017 International Workshop of the Chinese Academy of Medical Sciences (CAMS) Initiative for Innovative Medicine on Tumor Immunology held in Beijing, China, on May 12, 2017, a number of speakers reported new findings and ongoing studies on immune-related diseases such as cancer, fibrotic disease, diabetes, and others. A considerably insightf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Nevertheless, challenges still exist in recognizing the coexisting targets on a tumor cell and selecting the proper epitope in TanCAR therapy 128 , 129 . In addition, oncolytic viruses can infect the host, replicate and damage certain tumor cells without harming normal cells 130 , 131 . Evidence has shown that tumor cells can be killed via the new viral proteins integrated in its cytoplasm presented by the major histocompatibility complex class I molecules, and thereafter being recognized and destroyed by CD8 T cells 130 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, challenges still exist in recognizing the coexisting targets on a tumor cell and selecting the proper epitope in TanCAR therapy 128 , 129 . In addition, oncolytic viruses can infect the host, replicate and damage certain tumor cells without harming normal cells 130 , 131 . Evidence has shown that tumor cells can be killed via the new viral proteins integrated in its cytoplasm presented by the major histocompatibility complex class I molecules, and thereafter being recognized and destroyed by CD8 T cells 130 .…”
Section: Discussionmentioning
confidence: 99%
“…IL-17A is a proinflammatory cytokine produced by the Th17 subset of T-cells 1 . Th17 cells are an identified subset of T helper cells associated with chronic inflammation, autoimmune disorders, fibrotic disease, and cancer1., 2., 3., 4.. Therefore, the development of IL-17A-targeted therapeutic agents has important clinical benefits 5 .…”
Section: Introductionmentioning
confidence: 99%